In vivo enrichment of busulfan-resistant germ cells for efficient production of transgenic avian models - Kim, Young Min (Sci Rep, 2021)
Most transgenic animals are generated using a genome-modified stem cell system and genome modification directly in embryos. Although this system is well-established in the development of transgenic animals, donor cell-derived transgenic animal production is inefficient in some cases. Especially in avian models such as chickens, the efficiency of transgenic animal production through primordial germ cells (PGCs) is highly variable compared with embryonic manipulation of mammalian species. Because germ cell and germline-competent stem cell-mediated systems that contain the transgene are enriched only at the upstream level during cell cultivation, the efficiency of transgenic animal production is unreliable. Therefore, we developed an in vivo selection model to enhance the efficiency of transgenic chicken production using microsomal glutathione-S-transferase II (MGSTII)-overexpressing PGCs that are resistant to the alkylating agent busulfan, which induces germ cell-specific cytotoxicity. Under in vitro conditions, MGSTII-tg PGCs were resistant to 1 μM busulfan, which was highly toxic to wild-type PGCs. In germline chimeric roosters, transgene-expressing germ cells were dominantly colonized in the recipient testes after busulfan exposure compared with non-treated germline chimera. In validation of germline transmission, donor PGC-derived progeny production efficiency was 94.68%, and the transgene production rate of heterozygous transgenic chickens was significantly increased in chickens that received 40 mg/kg busulfan (80.33–95.23%) compared with that of non-treated germline chimeras (51.18%). This system is expected to significantly improve the efficiency of generating transgenic chickens and other animal species by increasing the distribution of donor cells in adult testes.